Usefulness of Free Tissue Transfer for the Reconstruction of Extensive Thigh Defects - Choi, Jae-Min; Lee, Kyeong-Tae; Mun, Goo-Hyun (Journal of Reconstructive Microsurgery, 2023)
Background Despite the increasing popularity of free tissue transfer, thigh defects have been alienated from their potential indication, owing to the abundance of regional reconstruction options. However, some challenging situations where locoregional modalities may lead to suboptimal outcomes often require free flap. Due to lacking studies regarding microvascular reconstruction of thigh defects, this study aimed to investigate the versatility of free tissue transfer for reconstruction of thigh defects.Methods A retrospective review was performed for patients who underwent microvascular reconstruction of thigh defects between 2003 and 2021. Their demographics and operation-related data were summarized and postoperative outcomes were evaluated.Results Sixty-five patients were analyzed, with a median follow-up period of 15.5 months. Most common situations requiring free tissue transfer were extensive defects, followed by large dead space with exposure of major neurovascular bundle and chronic wounds surrounded by unhealthy regional tissue. Defects were most frequently located in the anterior compartment horizontally and in the distal thigh vertically. The median surface area of the defects was 180.0 cm2. The latissimus dorsi musculocutaneous and thoracodorsal artery perforator flaps were the two most commonly used flaps. Reliable recipient vessels could generally be easily found in the vicinity of defects. Overall complications developed in 12 cases (18.5%), including two of partial flap necrosis. No total flap loss was encountered.Conclusion Free tissue transfer could provide reliable outcomes and facilitate rapid recovery, and could be actively considered for reconstruction of thigh defects in situations unfavorable to the locoregional option.
Keywords: free flaps; microvascular reconstruction; thigh; defects